2009
DOI: 10.1088/1464-4258/11/8/085403
|View full text |Cite
|
Sign up to set email alerts
|

Poincaré-sphere representation of phase-mostly twisted nematic liquid crystal spatial light modulators

Abstract: We establish necessary conditions in order to design a phase-only wave front modulation system from a liquid crystal display. These conditions determine the dependence of the polarization state of the light emerging from the display on the addressing gray level. The analysis, which is carried out by means of the coherence-matrix formalism, includes the depolarization properties of the device. Two different types of polarization distributions at the output of the liquid crystal cells are found. This approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Furthermore, a few studies point out that the state of polarization (SOP) of an input light beam can vary after interacting with an SLM [14,22]. This modulated SOP can alter the polarization response of the SLM [6,14,23]. It is observed that the earlier reported techniques on Jones matrix determination of the SLM require four-shot imaging, i.e., four different sets of measurements [8,24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a few studies point out that the state of polarization (SOP) of an input light beam can vary after interacting with an SLM [14,22]. This modulated SOP can alter the polarization response of the SLM [6,14,23]. It is observed that the earlier reported techniques on Jones matrix determination of the SLM require four-shot imaging, i.e., four different sets of measurements [8,24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to characterize intensity-based polarization characterization of a sample, several techniques are available, that is, Mueller matrix imaging (MMI) [19,20], Stokes polarimetry [21], and Poincare sphere [22,23]. Mueller matrix imaging (MMI) is the most commonly used polarimetric technique in order to characterize the full polarimetric characteristics of a depolarizing medium.…”
Section: Introductionmentioning
confidence: 99%
“…The Poincare sphere can represent any possible polarization state or Stokes vector. Poincare sphere has been successfully utilized in polarization metrology , representation of phase by twisted nematic liquid crystal spatial light modulators , analysis of fiber polarization mode dispersion , DOP surfaces and maps for analysis of depolarization , evolution of linear and circular polarization in scattering environments , hybrid elliptically polarized vector fields and hybrid polarized vector beams , representation for spatially varying birefringence , and representation of the fixed polarizer rotating retarder optical system. Additionally, detection and diagnosis of chronic disease has also been performed successfully by projecting different polarization states of light on Poincare sphere .…”
Section: Introductionmentioning
confidence: 99%